Prevalence and characterization of extended‐spectrum beta‐lactamase‐producing Enterobacteriaceae in spring waters. (1st December 2015) - Li, S.; Zhu, Z.C.; Wang, L.; Zhou, Y.F.; Tang, Y.J.; Miao, Z.M.
Abstract: The purpose of this study was to investigate the prevalence and characterization of extended‐spectrum beta‐lactamases (ESBL)‐producing Enterobacteriaceae from spring waters in Mountain Tai of China. ESBL‐producing Enterobacteriaceae were found in four out of 50 sampled spring waters (4/50, 8·0%) and a total of 16 non‐duplicate ESBL‐producing Enterobacteriaceae were obtained, including 13 Escherichia coli ( E. coli ) and three Klebsiella pneumoniae ( Kl. pneumoniae ). All 16 nonduplicate ESBL‐producing Enterobacteriaceae isolates harboured genes encoding CTX‐M ESBLs, among which six expressed CTX‐M‐15, five produced CTX‐M‐14, three produced CTX‐M‐55 and two expressed CTX‐M‐27. Four multilocus sequence types (ST) were found and ST131 was the dominant type (8/16, 50·0%). Taken together, the contamination of ESBL‐producing Enterobacteriaceae were present in spring waters of Mountain Tai. Significance and Impact of the Study: The results indicated that spring waters could become a reservoir of antibiotic resistant bacteria and contribute to the spread of antimicrobial‐resistant bacteria via drinking water or food chain. In addition, wastewater discharge of restaurants or hotels may be an important contribution source of antibiotic resistant bacteria in spring waters.